2021
DOI: 10.1513/annalsats.202010-1321oc
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Relates to Airway Pathology in Children with Wheezing

Abstract: Rationale: Outdoor air pollution contributes to asthma development and exacerbations; yet, its effects on airway pathology have not been defined in children. Objective:To explore the possible link between air pollution and airway pathology, we examined retrospectively the relation between environmental pollutants and pathological changes in bronchial biopsies of children undergoing a clinically indicated bronchoscopy.Methods: Structural and inflammatory changes (Basement Membrane-BM thickness, epithelial loss,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…With the deterioration in air quality, the global incidence of asthma has been increasing. 26 In that context, airway remodeling as an important common feature of asthma, especially severe refractory asthma, remains a challenge for treatment and clinical management. 7 Currently, the airway epithelium is considered to play significant roles in the progression of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…With the deterioration in air quality, the global incidence of asthma has been increasing. 26 In that context, airway remodeling as an important common feature of asthma, especially severe refractory asthma, remains a challenge for treatment and clinical management. 7 Currently, the airway epithelium is considered to play significant roles in the progression of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, we recently observed a dual effect of long-term pollutants exposure on cellular inflammation in airway tissue: while in asthmatic children air pollution enhances eosinophilic inflammation in bronchial mucosa, in non-asthmatic ones it associates with reduced numbers of both eosinophils and neutrophils ( 24 ). Altogether the results of the two studies suggest that air pollution can have a pro-inflammatory effect in susceptible subjects (asthmatics) while, at the same time, impairing innate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the nerve density and airway reactivity in adult age was linked to IL-5 exposure during embryogenesis [21,22]. Today, it is widely assumed that poor indoor air quality and exposure to allergens are the main reasons for developing childhood asthma [23][24][25][26][27][28]. Rhinovirus infection at a young age presents another risk factor to develop asthma later in life [29].…”
Section: Early Events Leading To Asthma and Airway Wall Remodeling In...mentioning
confidence: 99%
“…The authors concluded that the current asthma therapies do not affect airway wall remodeling in children with asthma. In another study, structural changes of the airways were investigated in biopsies obtained from 53 children with wheezing and compared to 45 children without wheezing [26]. Prolonged exposure to PM10 (10 microns) resulted in increased thickness of the basement membrane and eosinophilic inflammation in wheezing children.…”
Section: Early Events Leading To Asthma and Airway Wall Remodeling In...mentioning
confidence: 99%